Mondragon’s cooperativism community paradigm: Observing the roots to rethink the future - Loyola Idiakez, Aitzol (Cooperativismo & Desarrollo, 2018)
Purpose: The article aims at providing reflection with respect to Mondragon’s cooperativism self-managed community background and connects it with Jeremy Rifkin and Henry Mintzberg’s deliberations about economic and community self-management.Description: The article explains the key factors on which Mondragon’s cooperativism community paradigm was built and analyzes its implementation during the first decades of the 20th century.Point of view: The article takes a look at the origins of Mondragon’s cooperative experience; it analyzes how the community ideal that underlay the cooperative movement was put in practice. It’s a historical analysis that makes it possible to rethink the future focusing on the community.Conclusion: The analysis allows concluding that Mondragon’s cooperative movement supposes an attractive perspective to rethink 21st century’s society, just as contemporary authors like J. Rifkin and H. Mintzberg suggest.
Keywords: self-management; community; cooperativism; Mondragon; social transformation